ChemInform Abstract: Copper‐Mediated Cyanation of Indoles and Electron‐Rich Arenes Using DMF as a Single Surrogate. Issue 49 (December 2015) - Zhang, Lianpeng; Lu, Ping; Wang, Yanguang
Abstract: Cyanation of indoles and 6‐azaindoles by DMF yields the corresponding 3‐cyano derivatives.